2011
DOI: 10.4049/jimmunol.1001210
|View full text |Cite
|
Sign up to set email alerts
|

CC and CXC Chemokines Induce Airway Smooth Muscle Proliferation and Survival

Abstract: The increase in airway smooth muscle (ASM) mass is a major structural change in asthma. This increase has been attributed to ASM cell (ASMC) hyperplasia and hypertrophy. The distance between ASMC and the epithelium is reduced, suggesting migration of smooth muscle cells toward the epithelium. Recent studies have suggested a role of chemokines in ASMC migration toward the epithelium; however, chemokines have other biological effects. The objective of the current study is to test the hypothesis that chemokines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…IL-8 has been reported to trigger calcium release, contraction, and migration in BSMCs (47-49) through its functional receptors (50, 51). Halwani et al (52) reported that chemokines (including IL-8) may contribute to airway remodeling of asthma by enhancing the number and survival of BSMCs. However, the role of IL-8 on YKL-40-related remodeling of asthma remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 has been reported to trigger calcium release, contraction, and migration in BSMCs (47-49) through its functional receptors (50, 51). Halwani et al (52) reported that chemokines (including IL-8) may contribute to airway remodeling of asthma by enhancing the number and survival of BSMCs. However, the role of IL-8 on YKL-40-related remodeling of asthma remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CCR1, when stimulated by its ligand CCL5, regulated ASM cell proliferation via p42/p44 MAPK activation (55). Similarly, CCR3, when stimulated by its ligand CCL11/eotaxin, regulated ASM cell migration and proliferation via p42/p44 MAPK activation (55,70,136). The CCR7-CCL19 interaction increased ASM cell migration (73).…”
Section: Role Of Chemokine Receptors In Asm Cellsmentioning
confidence: 99%
“…Both CC and CXC chemokine receptors have also been found expressed in ASM cells, where they have been involved mainly in migration and proliferation processes. CCR1, when stimulated by its ligand CCL5, regulated ASM cell proliferation via p42/p44 MAPK activation (55). Similarly, CCR3, when stimulated by its ligand CCL11/eotaxin, regulated ASM cell migration and proliferation via p42/p44 MAPK activation (55,70,136).…”
Section: Role Of Chemokine Receptors In Asm Cellsmentioning
confidence: 99%
“…Here, in contrast to the substantial data on increased ASM cell proliferation, there is much less information on apoptosis per se. Some studies have reported reduced rates of ASM apoptosis following exposure to Th17-associated cytokines (39), IL-8, eotaxin, and monocyte inflammatory protein-1a (107), as well as with TRPV1 agonist (354), extracellular laminin (313), and ␥-glutamyl transpeptidase-1 (GGT1) antagonism (83). However, several other studies have found that mechanisms such as phosphatase and tensin homolog deleted on chromosome 10 (182), PPAR-␥ (73), collagens (274), and vitamin D (50) modulate ASM cell proliferation but do not influence apoptosis.…”
Section: L922mentioning
confidence: 99%